Seven new species of the cicada genus Guyalna Boulard & Martinelli, 1996 (Hemiptera: Cicadidae: Fidicinini) with a re-description of the type species - Ruschel, Tatiana Petersen (Zootaxa, 2017)
The knowledge of Guyalna Boulard & Martinelli is improved with the description of seven new species (Guyalna aurora Ruschel sp. nov., Guyalna flavantica Ruschel sp. nov., Guyalna pilosa Ruschel sp. nov., Guyalna principis Ruschel sp. nov., Guyalna sakakibari sp. nov., Guyalna spinula Ruschel sp. nov. and Guyalna tenebrae Ruschel sp. nov.); Fidicinoides fumea (Distant, 1883) is transferred to Guyalna, redescribed and the male genitalia is described for the first time; and the type species, G. bonaerensis (Berg, 1879), is re-described, including the first description of the male genitalia and of female characters.